2013
DOI: 10.4236/ojog.2013.31014
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer screening among female undergraduates and staff in the Niger delta region of Nigeria

Abstract: A significant decrease in the incidence of cervical cancer and mortality is expected when all eligible women have access to regular Screening tests. Factors that can influence participation rate include: acceptability, accessibility, screening interval, promotion of screening among others. This study is aimed at the assessment of the risk factors for cervical cancer, the knowledge and level of utilization of cervical cancer screening among female staff and female undergraduates of Niger Delta University. A sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 23 publications
5
15
0
Order By: Relevance
“…The risk factors identified in this study were similar to previous studies [7] [21] [23], which are likely to expose the female undergraduate students to the risk of contracting Human Papilloma Virus (HPV) infection and possible progression to cervical cancer.…”
Section: Discussionsupporting
confidence: 73%
“…The risk factors identified in this study were similar to previous studies [7] [21] [23], which are likely to expose the female undergraduate students to the risk of contracting Human Papilloma Virus (HPV) infection and possible progression to cervical cancer.…”
Section: Discussionsupporting
confidence: 73%
“…The most common reason for not assessing Pap smear screening services was the perception that the subjects were not at risk of the disease. Also in the study [11] conducted on cervical cancer screening among female undergraduates and staff in the Niger delta region of Nigeria, findings revealed that out of all the respondents that were used for the study only 12% of the respondents has had at least one Pap test in the past. The commonest reasons for uptake of screening were; when it is free or subsidized 27.3% as part of a general screening program 27.3%, Doctor's request 18.2% and self-conviction 18.2%.…”
Section: Introductionmentioning
confidence: 99%
“…They also use reproductive health services for post-natal checkup and family planning or when faced with various gynaecological problems. A study by Ibrahim, Owoeye and Kalada (2013) at Niger Delta Nigeria revealed that, almost half of the respondents, considered themselves healthy and did not see any reason to subject themselves to any form of cervical cancer screening. Similarly, a study by Basu, Sarkar, Mukherjee, Ghoshal, Mittal and Biswas (2006) in India found that, the most common reasons cited for non-attendance to cervical cancer screening was reluctance to go for medical test in the absence of any symptoms and apprehension to have a test that detects cancer.…”
Section: No Sign Of Cervical Cancermentioning
confidence: 99%
“…Majority said that, "this will reduce time wastage since we will have to go to the hospital once and receive two different services and also reduce cost". A study by Ibrahim, Owoeye and Kalada (2013) at Niger Delta Nigeria revealed that, the commonest reasons for uptake of screening was when it was free or subsidized or as part of a general screening program.…”
Section: Free Servicesmentioning
confidence: 99%
See 1 more Smart Citation